On the pitting behaviour of laser powder bed fusion prepared 316L stainless steel upon post-processing heat treatments. (1st April 2022) - Wang, Ke; Chao, Qi; Annasamy, Murugesan; Hodgson, Peter D.; Thomas, Sebastian; Birbilis, Nick; Fabijanic, Daniel
Abstract: Type 316L stainless steel manufactured by laser powder bed fusion (LPBF) in conjunction with appropriate post-treatment has been demonstrated to offer superior pitting resistance and a distinct pitting mechanism compared to wrought 316L. This work examines the effect of post-processing annealing time, temperature and microstructural changes on the pitting behaviour of LPBF 316L using potentiodynamic and potentiostatic polarisation in 0.6 M NaCl. Preferential pitting at melt pool boundaries was observed, due to heterogeneity of micro-strain or lattice imperfection. High temperature annealing resulted in the transformation of amorphous oxides with associated Cr-depletion, leading to a reduction of E pit and E rp . Highlights: An essentially porosity-lean 316L stainless steel was prepared by LPBF and subjected to cyclic potentiodynamic and potentiostatic polarisation analysis in 0.6 M NaCl. Preferential pitting at melt pool boundaries was observed, due to heterogeneity of micro-strain or lattice imperfection. An increased pitting potential was detected in the LFBF 316L after annealing at 800 °C for 2 h despite the presence of sigma phase formation. Simultaneous formation of MnS precipitates and coarsened oxides was observed after annealing at 1000–1100 °C and the latter predominantly contributed to a reduced pitting potential.